Anemoside B4 Protects against Acute Lung Injury by Attenuating Inflammation through Blocking NLRP3 Inflammasome Activation and TLR4 Dimerization. (4th December 2020) - Yuan, Renyikun; He, Jia; Huang, Liting; Du, Li-Jun; Gao, Hongwei; Xu, Qiongming; Yang, Shilin
Abstract : Acute lung injury (ALI) is an acute inflammatory process in the lung parenchyma. Anemoside B4 (B4) was isolated from Pulsatilla, a plant-based drug against inflammation and commonly applied in traditional Chinese medicine. However, the anti-inflammatory effect and the mechanisms of B4 are not clear. In this study, we explored the potential mechanisms and anti-inflammatory activity of B4 both in vitro and in vivo . The results indicated that B4 suppressed the expression of iNOS, COX-2, NLRP3, caspase-1, and IL-1 β . The ELISA assay results showed that B4 significantly restrained the release of inflammatory cytokines like TNF- α, IL-6, and IL-1 β in macrophage cells. In addition, B4 rescued mitochondrial membrane potential (MMP) loss in (lipopolysaccharide) LPS plus ATP stimulated macrophage cells. Co-IP and molecular docking results illustrated that B4 disrupted the dimerization of TLR4. For in vivo results, B4 exhibited a protective effect on LPS and bleomycin- (BLM-) induced ALI in mice through suppressing the lesions of lung tissues, the release of inflammatory cytokines, and the levels of white blood cells, neutrophils, and lymphoid cells in the blood. Collectively, B4 has a protective effect on ALI via blocking TLR4 dimerization and NLRP3 inflammasome activation, suggesting that B4 is a potential agent for the treatment of ALI.